Isolation, Structural Elucidation, and Anti-HIV Activity of Daphnane Diterpenoids from Daphne odora - Otsuki, Kouharu; Li, Wei; Miura, Kasumi; Asada, Yoshihisa; Huang, Li; Chen, Chin-Ho; Lee, Kuo-Hsiung; Koike, Kazuo (Journal of natural products (Washington, D.C.), 2020)
Five new [daphneodorins D–H (1, 5, and 10–12)] and seven known daphnane diterpenoids (2–4 and 6–9) were isolated from Daphne odora. The structures of the new compounds were elucidated by extensive physicochemical and spectroscopic analysis. The isolated compounds were evaluated for their anti-HIV activity against HIV-1 infection of MT4 cells. Nine daphnane diterpenoid orthoesters (1–9) showed potent anti-HIV activity with EC50 values of 1.5–7.7 nM.